Peculiarities of injection phenomena in heavily doped silicon structures and development of radiation-resistant diode temperature sensors - Shwarts, Yu.M.; Sokolov, V.N.; Shwarts, M.M.; Venger, E.F. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
To explain the experimental behaviour of differential characteristics (ideality factor, differential resistance) before and after radiation influence, a theoretical model of injection current flow mechanisms for the silicon diode temperature sensors (DTSs) is proposed. The observed nonmonotonic dependencies of the ideality factor on the current are described well by the influence of generation-recombination and drift current components to the diffusion current of the minority carriers. The developed model allowed to find characteristic lifetimes of the minority carriers in the base and in the space-charge region of the diode structure with heavily doped base and emitter regions. Investigations of electrophysical and metrological characteristics of the DTSs allowed to reveal such operating regimes that are characterised by minimal influence of radiation on the device thermometric characteristics.